2000
DOI: 10.1002/1098-2736(200011)37:9<963::aid-tea6>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

The effects of professional development on science teaching practices and classroom culture

Abstract: The current science education reform movement emphasizes the importance of professional development as a means of improving student science achievement. Reformers have developed a vision for professional development based upon intensive and sustained training around concrete tasks that is focused on subject‐matter knowledge, connected to specific standards for student performance, and embedded in a systemic context. Using data from a National Science Foundation Teacher Enhancement program called the Local Syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

21
426
2
7

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 577 publications
(471 citation statements)
references
References 10 publications
21
426
2
7
Order By: Relevance
“…Supovitz and Turner's (2000) findings indicate that content preparation has a powerful influence on teaching practices and classroom culture. Higher education faculty members bring a strong content orientation that has been shaped by common pedagogical and assessment practices in their particular disciplines, as well as discipline-specific definitions of 'expertise. '…”
Section: Faculty Understanding Of Pblmentioning
confidence: 99%
“…Supovitz and Turner's (2000) findings indicate that content preparation has a powerful influence on teaching practices and classroom culture. Higher education faculty members bring a strong content orientation that has been shaped by common pedagogical and assessment practices in their particular disciplines, as well as discipline-specific definitions of 'expertise. '…”
Section: Faculty Understanding Of Pblmentioning
confidence: 99%
“…Providing time for teachers to meet also increases the likelihood that they will have opportunities to learn from and share expertise with colleagues about instruction (Kruse, 2001). Shared planning time can positively influence teachers' perception of the school (Warren & Muth, 1995) and has been linked to classroom implementation of reforms (Supovitz & Turner, 2000;Uekawa, Aladjem, & Zhang, 2006).…”
Section: How People and Places Could Affect The Success Of Alignmentmentioning
confidence: 99%
“…Researchers have posited teacher beliefs towards reform-based learning environments influence teaching practices and beliefs play a critical role with influencing alignment of practice to constructivist learning environments Luft 2001). Similarly, teachers use reform-based practices and an investigatory classroom culture if they are more sympathetic towards reform (Supovitz & Turner, 2000). Despite all four participants in this study having beliefs supportive of constructivist learning environments, not all of the teachers aligned as high in practice to constructivist principles when teaching a PBL unit.…”
Section: Discussionmentioning
confidence: 79%
“…However, changing beliefs is difficult (Pajares, 1992) and is unlikely to occur due to a professional development workshop. Similarly, Supovitz and Turner (2000) posit that teacher attitudes towards reform influence teaching practices. They found that teachers more sympathetic towards reform more frequently use inquiry-based practices and maintain a more investigatory classroom culture.…”
mentioning
confidence: 99%
See 1 more Smart Citation